HUMAN UTERINE LAVAGE: EMBRYO SAFETY AND FIRST LIVE BIRTHS FROM IN VIVO CONCEIVED GENETICALLY SCREENED BLASTOCYSTS. - Najmabadi, Sam; Rivas, Jose L.; Angle, Marlane; Cohen, Jacques; Nadal, Alex; Bastu, Ercan; Munne, Santiago; Carson, Sandra Ann; Buster, John E.; Nakajima, Steven T. (ELSEVIER SCIENCE INC, 2020)
76th Virtual Scientific Congress and Expo of the American-Society-for-Reproductive-Medicine (ASRM), ELECTR NETWORK, OCT 17-21, 2020